A breakdown of sector performance of the Visegrad countries and Germany in light of structural convergence. Śląski Przegląd Statystyczny = Silesian Statistical Review, 2013, Nr 11 (17), s. 31-48 - Úradníček, Vladimir; Zimková, Emília (Silesian Statistical Reviev, 2013)
The aim of this contribution is to analyze a breakdown of sector performance of the Visegrad countries and Germany in light of structural convergence. The macroeconomic view on structural convergence was researched by the estimation of business cycle synchronization of pairs of countries. The microeconomic aspect of structural convergence is characterized by the breakdown of sector performance of the analyzed countries and the application of the Krugman specialization index
Keywords: business cycle synchronization; sector breakdown; Krugman specialization index; synchronizacja cyklów gospodarczych; załamanie funkcjonowania sektorowego; wskaźnik specjalizacyjny Krugmana